2017
DOI: 10.1038/nbt.3870
|View full text |Cite
|
Sign up to set email alerts
|

A wellness study of 108 individuals using personal, dense, dynamic data clouds

Abstract: We collected personal, dense, dynamic data for 108 individuals over 9 months, including whole genome sequence; clinical tests, metabolomes, proteomes and microbiomes at three time points; and daily activity tracking. Using these data we generated a correlation network and identified communities of related analytes that were associated with physiology and disease. We demonstrate how connectivity within these communities identified known and candidate biomarkers, e.g. gamma-glutamyltyrosine was densely interconn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
329
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(337 citation statements)
references
References 64 publications
8
329
0
Order By: Relevance
“…A precise understanding of cell‐ and individual‐intrinsic variability, the environmental sources of variability, and how these effects are propagated and accumulate throughout life will also allow to reveal to what extent environmental or behavioral intervention could have an impact on modulating disease risks . This way, personalized monitoring and adaptation of lifestyle factors such as diet or physical activity could enable the combination of precision medicine with disease prevention, the ultimate goal of successful health care management. That this is achievable has been successfully exemplified by the Pioneer 100 Wellness Project (P100) and the Blue Zones Vitality Project, which showed that modulating the environment and behavior of a population can indeed lead to improved health and life‐expectancy.…”
Section: Resultsmentioning
confidence: 99%
“…A precise understanding of cell‐ and individual‐intrinsic variability, the environmental sources of variability, and how these effects are propagated and accumulate throughout life will also allow to reveal to what extent environmental or behavioral intervention could have an impact on modulating disease risks . This way, personalized monitoring and adaptation of lifestyle factors such as diet or physical activity could enable the combination of precision medicine with disease prevention, the ultimate goal of successful health care management. That this is achievable has been successfully exemplified by the Pioneer 100 Wellness Project (P100) and the Blue Zones Vitality Project, which showed that modulating the environment and behavior of a population can indeed lead to improved health and life‐expectancy.…”
Section: Resultsmentioning
confidence: 99%
“…To further qunatify these differences, projects have been initiated to extend such analyses to thousands of individuals, characterizing preterm births, inflammatory bowel disease and type 2 diabetes 53 . In a similar vein, two separate groups recently profiled genetic and metabolomics data: one of these calculated polygenic risk scores for over 100 individuals and correlated these with measurements of metabolites 54 , whereas the other identified rare deleterious variants in healthy volunteers that correlated with outliers of individual metabolites and metabolic pathways 55 . Additionally, as reference databases of omics data for healthy individuals become available (as are already available for exome 56 , genome (for example, the Genome Aggregation Database (gnomAD)) and RNA-seq 57 data), it will become easier to interpret individual-level data in the context of these control cohorts.…”
Section: Narrowing Causal Mechanisms In Common Diseasementioning
confidence: 99%
“…However, the adoption of clinical genomics has expanded rapidly over the past few years from the first successful diagnosis 1 to multi-institutional and international adoption 72 . In the same vein, longitudinal multi-omics profiling, with its first recent research examples 6,54 , may similarly emerge as a clinical tool.…”
Section: Challengesmentioning
confidence: 99%
“…Thus, where statistical powering is a key consideration in research metabolomics, clinical metabolomics is a true n‐of‐1 analysis. Untargeted clinical metabolomic profiling of individual patient samples has found early application in the screening of inherited metabolic diseases, but other uses, such as probing of undiagnosed cases for disease insights, as well as health and wellness screenings, have started to emerge …”
Section: Considerations For Metabolomics Applications In Research Andmentioning
confidence: 99%
“…In addition to combining metabolomic and genomic data, a larger trend is to seamlessly integrate all patient information, such as test results from traditional clinical biochemistry (eg, enzymatic assays, protein assays), clinical ‘omics, and microbiome profiling. The combination of clinical metabolomics testing results, clinical biochemistry, and other ‘omics data streams has been shown to offer superior diagnostic power, in both IEM and wellness screenings, relative to the individual methods performed in isolation.…”
Section: Integration Into Clinical Medicinementioning
confidence: 99%